2014
DOI: 10.1111/pbr.12227
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium tolerance in lentil (Lens culinaris Medik.) with monogenic inheritance pattern

Abstract: The objectives of this study were to determine genetics of Al tolerance and whether the Al tolerance observed is governed by the same gene. The lines 'L-7903' and 'L-4602' have been developed through breeding programme as Al-tolerant lines. These lines showed maximum root regrowth and minimum accumulation of Al and callose as compared to sensitive genotypes ('BM-4' and 'L-4147'). Al tolerance in the parents, F 1 , F 2 and backcross generations was estimated using the regrowth of the primary root after staining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Callose accumulation in roots has also been known as a sensitive indicator of A1 toxicity and can be readily detected by fluorescence microscopy [ 62 , 36 ]. In controls (absence of Al), resistant and sensitive genotypes showed a negligible fluorescence, whereas strong fluorescence signals (callose accumulation) were detected in roots after exposure to 74 and 148 μm Al for 48 h. Callose was observed slightly lower in resistant breeding lines (L-7903, L-4602 and ILWL-185) than in sensitive cultivars (BM-4, L-4147 and ILWL-436) ( Fig 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Callose accumulation in roots has also been known as a sensitive indicator of A1 toxicity and can be readily detected by fluorescence microscopy [ 62 , 36 ]. In controls (absence of Al), resistant and sensitive genotypes showed a negligible fluorescence, whereas strong fluorescence signals (callose accumulation) were detected in roots after exposure to 74 and 148 μm Al for 48 h. Callose was observed slightly lower in resistant breeding lines (L-7903, L-4602 and ILWL-185) than in sensitive cultivars (BM-4, L-4147 and ILWL-436) ( Fig 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…These accessions were chosen based on previous studies, where L-4602 was found to be Al tolerant breeding line developed at Indian Agricultural Research Institute (IARI), India whereas BM-4 was found to be Al sensitive cultivar, which was developed from the cross between ILL-5888 (improved landrace) and ILL-5782 (breeding line) at International Center for Agricultural Research in the Dry Areas (ICARDA), Syria [7,90,91]. ILWL-15 is a mineral rich wild accession which was originated in France and was reported to be moderately tolerant to Al stress [7,92].…”
Section: Materials and Methods Plant Materialsmentioning
confidence: 99%
“…Two common strategies to alleviate Al toxicity are: soil liming [ 4 , 5 ] and crop breeding to develop resistant genotypes [ 6 , 7 ]. Amongst these, development of Al-resistant genotypes is considered as the most effective, economical and environmentally acceptable strategy to maintain sustainable production under Al toxic soils.…”
Section: Introductionmentioning
confidence: 99%
“…Efficient screening technique plays an important role to get appropriate differential response in genotypes reflected via stress indicating parameters. In our previous Al stress studies, root re-growth, callose deposition, Al accumulation, antioxidant synthesis and organic acid exudation were efficiently used as identification parameters for Al toxicity resistance [ 7 , 15 , 16 , 17 ]. Yusuf et al [ 18 ] assessed Al-resistance of wheat cultivars based on photosynthetic (maximum quantum yield of PSII), osmotic (leaf water potential, electrolyte leakage) and physio-biochemical (lipid peroxidation, hydrogen peroxide production, antioxidant enzyme synthesis and proline content) traits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation